Enhancing University Administration and Communication Channels in Ghana: Keys to Higher Education Success - Poku, Michael B. Adusei (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2023)
This study investigates the administration and communication channels in Ghanaian universities, employing a qualitative research approach with a case study methodology, aiming to identify how administrative structures and communication effectiveness impact university goals; the findings reveal that strong, well-structured communication channels significantly enhance both academic performance and administrative efficiency, leading to the conclusion that improved communication practices are crucial for the overall success of university operations in Ghana.